2022
DOI: 10.1155/2022/4863756
|View full text |Cite
|
Sign up to set email alerts
|

Study on Antiseismic Effect of Different Thicknesses of Shock Absorption Layer on Urban Shallow Buried Double Arch Rectangular Tunnel

Abstract: With the development of urban tunnels, more and more studies focus on the antiseismic design of tunnels. Setting up a shock absorption layer is a very effective means in the earthquake resistance of an urban tunnel. In this paper, in order to study the influence of the thickness of a shock absorption layer on the antiseismic effect of the urban shallow buried double arch rectangular tunnel, the Tengzhou–Fenghuang tunnel is used as the research background. Firstly, the model is established by finite element sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…The seismic considerations for tunnel construction can be generally divided into three categories [21][22][23][24]. In general, the first category is to set a shock protective layer between the tunnel lining and the surrounding soils [25][26][27][28]. The second category is to optimize the damping performance of the tunnel.…”
Section: Case Of Earthquake Damage Time Locations Resultsmentioning
confidence: 99%
“…The seismic considerations for tunnel construction can be generally divided into three categories [21][22][23][24]. In general, the first category is to set a shock protective layer between the tunnel lining and the surrounding soils [25][26][27][28]. The second category is to optimize the damping performance of the tunnel.…”
Section: Case Of Earthquake Damage Time Locations Resultsmentioning
confidence: 99%
“…An et al [16], in 2021, established an ABAQUS finite element model to clarify the influence of fiber-reinforced concrete lining structure on the seismic performance of an urban shallow-buried rectangular tunnel. Additionally, Jian et al [17], in 2022,applied the finite element method to examine the influence of the thickness of a shock absorption layer on the seismic effect of an urban shallow-buried double-arch rectangular tunnel. Moreover, Liu et al [18], in 2022, employed full dynamic time history analysis to investigate the interaction in the transversal direction of an arched tunnel buried in a stratified soil in Hohhot, China.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, due to the presence of underground structures, which change the nearby surface site conditions, seismic waves produce an ampli cation e ect during transmission, thus a ecting the seismic response of adjacent structures underground and at the surface. Numerical simulations and experimental studies have been carried out by a large number of scholars on the causes of seismic damage in tunnels and their in uencing [4][5][6]. Wang and Cai [7] explored the dynamic response law of tunnels at di erent wavelength ratios by the spectral element method, and the results indicated that the velocity amplification is proportional to the tunnel diameter, and tunnels with larger diameters are more prone to damage under seismic action.…”
Section: Introductionmentioning
confidence: 99%